Assessing the Prognostic Value of the Neutrophil-to-Lymphocyte Ratio in Stage I Non-Small-Cell Lung Cancer with Complete Resection - Wei Liu; Tiantian Zhang; Li Li; Jue Zou; Chunhua Xu (Canadian Respiratory Journal)
Purpose. To explore the prognostic value of the neutrophil-to-lymphocyte ratio (NLR) in stage I non-small-cell lung cancer (NSCLC) undergoing surgery. Patients and Methods. Between 2014 and 2016, a total of 190 patients with postoperative pathology of stage I NSCLC who underwent radical surgery at Nanjing Chest Hospital were studied. Clinical data were analyzed and classified into low-risk, moderate-risk, and high-risk groups based on independent risk factors to assess the prognosis. Results. NLR was associated with histological type and gender, and patients with an elevated NLR have poor overall survival (OS). Lymphovascular invasion, red blood cell distribution width-standard deviation (RDW-SD), and carcinoembryonic antigen (CEA) were independent prognostic factors for progression-free survival (PFS) in postoperative patients with stage I NSCLC, while NLR, RDW-SD, and CEA were independent risk factors for OS. Both PFS and OS were shorter in the low-risk group than in the medium-risk and high-risk groups. Conclusions. NLR, RDW-SD, CEA, and lymphovascular invasion are independent risk factors for postoperative prognosis in patients with stage I NSCLC, and the combination has a predictive value.